Pelatihan Pembuatan Media Pembelajaran Di PGRI Kecamatan Cisarua - Maulana, Hanhan; Afrianto, Irawan; Setiyadi, Angga; Agustia, Richi Dwi; Hirawan, Dedeng (Indonesian Community Service and Empowerment Journal (IComSE), 2020)
ABSTRACT The purpose of this community service is to improve the quality of the teaching staff by conducting training for making learning media and learning applications to calculate student scores. This activity used 2 methods, first was the provision of basic knowledge then continued by the direct practice carried out by the participants. This training was divided into 4 sessions, the first session was an introduction to the basic components of the Windows operating system, the second session was learning Microsoft Word, the third session was learning processing scores with Microsoft Excel and the last session was making learning media using Microsoft Power point. Training material was given by the instructor, assisted by a mentor who accompanied the participants in following the material presented. Evaluation was done by giving questions in the form of case study. The trainees completed the case study with the timeframe given by each instructor. Based on the results of the evaluation and observation of the enthusiasm of the participants, it can be concluded that the training was in accordance with the expected objectives. By participating in this training, teachers had the ability to use computers to support their work in carrying out education and teaching in schools. Keywords: Community Service, Learning Media, Student Score Calculations, Microsoft Office Application, Teaching and Education ABSTRAK Tujuan dari pengabdian kepada masyarakat ini adalah Meningkatkan kualitas tenaga kependidikan dengan mengadakan pelatihan pembuatan media pembelajaran dan mempelajari aplikasi pengolahan nilai. Pengabdian kepada masyarakat ini menggunakan dua metode pertama adalah pemberian materi kemudian dilanjutkan dengan praktek langsung yang di lakukan oleh peserta. Pelatihan ini dibagi menjadi 4 sesi, sesi pertama adalah pengenalan terhadap komponen komponen dasar sitem operasi windows, sesi kedua adalah pembelajaran microsoft word, sesi ketiga adalah pembelajaran pengolahan nilai dengan microsoft excel dan sesi terakhir adalah pembuatan media pembelajaran menggunakan microsoft powerpoint. Materi pelatihan diberikan oleh pemateri dibantu dengan pendamping yang akan mendampingi peserta dalam mengikuti materi yang disampaikan. Evaluasi dilakukan dengan memberikan contoh soal berupa studi kasus. Peserta pelatihan menyelesaikan soal dengan rentan waktu yang di berikan oleh masing masing pemateri. Berdasarkan hasil evaluasi dan pengamatan terhadap antusiasme peserta dapat disimpulkan bahwa pelatihan ini sudah sesuai dengan tujuan yang diharapkan. Dengan pemberian pelatihan ini guru-guru di lingkungan PGRI Kec. Cisarua memiliki kemampuan dalam menggunakan perangkat komputer dalam mendukung tugasnya dalam melaksanakan pendidikan dan pengajaran di sekolah. Kata kunci: Pengabdian kepada masyarakat, Media pembelajaran, Pengolahan nilai siswa, Pelatihan penggunaan aplikasi Microsoft, Pendidikan dan Pengajaran